ESSENSIAL OIL DAN PEMANFAATAN ERYNGIUM FOETIDUM L. SEBAGAI OBAT TRADISIONAL - Silalahi, Marina (Jurnal Ilmiah Kesehatan Keperawatan, 2021)
Eryngium foetidum (EF) is one of the Apiaceae family that is used as medicine, vegetables and cooking spices. Plants that are used as medicine are directly or indirectly related to the content of secondary metabolites. The writing of this article is based on a literature review obtained from various online sources (mainly from google schoolar and scopus) and offline (books and other research results) using EF keywords, then synthesized to explain the benefits and bioactivity of EF. In ethnobotany fever, hypertension, headache, abdominal pain, asthma, arthritis, diarrhea, and malaria. The essential oil contained in EF is dominated by (E) -2-dodecenal, dodecanoic acid, trans-2-dodecanoic acid (9.7%), (E) -2-tridecenal, duraldehyde, and tetradecanal. EF's bioactivity has been proven to be anti-microbial, antioxidant and anti-natural. The ability of EF essential oils as an anti-microbial is very potential to be developed as a natural food preservative.